Collaborative Governance Model in Quik Wins Program Implementation Traffic Sector in Bandung - Tb. Anis Angkawijaya; Bambang Heru Purwanto; Eddy Jusuf Sp (Doctoral Program of Social Science Pasundan University, 2021)
Collaborative governance between institutions or stakeholders on the Collaborative Governance model in the implementation of the Quick Wins program in the field of traffic in the city of Bandung. still less effective. with indicators that communication is not going well, coordination is not sustainable, cooperation is not carried out, and agency sectoral egos. This study uses the Mix Method Research method with a concurrent embedded strategy, namely mixed research methods with qualitative data collection and analysis, quantitative carried out sequentially. Results of implementation effectiveness research Quick Wins program in the field of traffic, researchers examined 6 (six) effectiveness criteria, namely: 1) Standards/targets: stakeholder participation is still less involved 2). Community group network support resources have not fully participated 3). Communication: active information relations are still lacking, both formal and informal, 4). Implementing organizations are still lacking in involving all community groups, 5) Characteristics of implementing agents The attitudes and behavior of implementing agents are still not able to increase empowerment 6) The environment is still lacking support because people say business Traffic order is a matter for the Police and the Department of Transportation. ineffectiveness was found in 2 (two) criteria, namely Human Resources (49.38 %) and Communication. (47.61%). It is concluded that the effectiveness of the implementation of the Quick Wins program in the field of traffic in the city of Bandung is currently running quite well but is still not effective. The influencing factors are: 1) Commitment and consistency of the apparatus. 2) The seriousness and firmness of the apparatus, 3) Clear regulatory standards, 4) Support from community groups, 5). Quality and Quantity of Human Resources 6) The intensity of communication activities. Collaborative Governance model in the implementation of the Quick Wins program in the field of traffic in the city of Bandung, researchers examined 6 (six) principles/elements or dimensions of Collaborative Governance according to Horizon (2004:230). geared towards collaboration. 2) Institutional capacity: Community network support is not balanced enough to collaborate. 3) Collaborative leadership: building trust in public information disclosure is less institutionalized, the initiative to carry out leadership roles still relies on leader figures (Mayor or Kasat then). 4) Role as facilitator: Community elements are less involved in forums that do not represent various elements of interest, 5) Role of education and training: Less done within the framework of empowerment. 6) Institutional design: does not improve the quality of collaboration because the forum is still in the form of coordination and consultation. The Collaborative Governance model (Ansell & Gash 2007) needs modification by adding 3 (three) aspects to the collaboration process, namely: 1). Community empowerment, 2). Local community culture (local wisdom) 3). leadership (leadership) as a figure / role model. So that the Collaborative Governance model is recommended for a traffic board forum in the form of collaboration between stakeholders within the scope of the City of Bandung with duties and roles according to their respective functions and supported by private elements, experts/academics, observers, elements of.